1987
DOI: 10.1149/1.2100811
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Strain‐Related Effects during Growth of SiO2 Films on Silicon

Abstract: We analyze various aspects of the stress/strain present at the normalSi/SiO2 interface during the growth of the oxide which arise from the volume change associated with the transfer of Si atoms from the substrate to the oxide. This volume change is so high (126%) that it cannot be accommodated simply by elastic strain. Previously suggested viscoelastic stress relief models are incompatible with several experimental observations, require unrealistically low viscosity values, and have a number of conceptual di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…By investigating the oxide etch rates in dilute HF, they showed that the interface stress in oxides grown in dry O is higher than those grown in pyrogenic steam. We attribute this to the fact that the viscosity of OH-containing SiO is about two orders of magnitude less than that of dry SiO [49]. An oxide with a lower viscosity results in a lower film stress and therefore a higher .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…By investigating the oxide etch rates in dilute HF, they showed that the interface stress in oxides grown in dry O is higher than those grown in pyrogenic steam. We attribute this to the fact that the viscosity of OH-containing SiO is about two orders of magnitude less than that of dry SiO [49]. An oxide with a lower viscosity results in a lower film stress and therefore a higher .…”
Section: Discussionmentioning
confidence: 94%
“…All the trends of furnace and RTP oxides in the previous section can be explained by examining the role of physical stress at the SiO /Si interface. During the thermal growth of SiO , there is a 128% volume expansion from Si to SiO [25], and therefore the SiO film is compressed. The newly formed SiO pushes the previously grown SiO upwards.…”
Section: Stress Measurement Technique and Resultsmentioning
confidence: 99%
“…3 The thickness of this interfacial layer is on the order of 1 nm. However, the interface between a deposited oxide film and the underlying silicon is not nearly as perfect as that formed by thermal oxide.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that the uppermost one or two layers of silicon atoms beneath the silica scale were displaced up to about 0.015 nm (6.5%) from their lattice positions. 42 As mentioned above, the strains in the silica layer and silicon substrate are respectively due to elastic deformation and creep deformation. In such a case, the lattice of the silica scale is not obviously altered while the number of silicon atoms is changed, leading to the server deformation of the silicon lattice near the Si/SiO 2 interface.…”
Section: B Effect Of Constant Strain On Oxide Stress and Scale Thickmentioning
confidence: 93%